Dynamic capabilities for value creation from AI innovation ecosystem: a comparison between IFLYTKE and Amazon. Issue 2 (31st January 2023) - Chen, Yu; Chen, Yantai; Guo, Yanlin
Artificial intelligence (AI) is an important driving force for a new trend of scientific and technological revolution and industrial reform. This paper analyses the dynamic capabilities for value creation from AI innovation ecosystem and proposes a research framework: institutional environment-dynamic capabilities-ecosystem stage. Based on the empirical evidence from double case study in the typical AI ecosystem, IFLYTEK and Amazon, our research leads to the following three main conclusions: 1) the difference of institutional environment has an important impact on the development of AI ecosystem; 2) combination of dynamic capabilities can enable AI leading enterprises to promote ecosystem and comprehensive use of dynamic capabilities can promote ecological partners to participate in value creation; 3) different stages of innovation ecosystem development have different effects on dynamic capacities for value creation. Dynamic capabilities are vital for AI leading enterprises to maintain competitive advantage. As for practical implications, this research provides guidance on how to build dynamic capabilities of AI ecosystem, and gives enlightenment to how AI can construct dynamic capabilities for value creation to achieve sustainable development.